ANALISIS PENGARUH HADIST NABI MENGENAI MENGAMBIL MAKANAN YANG JATUH SEBELUM 5 DETIK MENURUT PANDANGAN KESEHATAN - Aqila, Zakiya Nada; Rhawil Wahid, Ray Febisyah; Aini, Nur; Fatmasari, Dewi; Siregar, Ahlun Nazi (Jurnal Pengabdian Kompetitif, 2024)
Humans require food to survive; it is a basic requirement. Whether these foods offer the best nutritional worth is yet unknown, though. Human food must have a variety of nutrients to sustain human life activities. Public health may be effectively improved by offering halal and sanitary meals. This satisfies both Islamic and health norms for delicious cuisine. Then there is dasit, which maintains that you can consume food that complies with Islamic precepts and the guidance of the Prophet Muhammad SAW. The literature review method used in this study involves the researchers doing a number of searches utilizing different kinds of material from literature, including books, encyclopedias, and papers. This seeks to identify different kinds of Key words: